ANALISIS TEGANGAN PADA FENDER KAPAL TIPE SETENGAH PIPA DENGAN FENDER TIPE M MENGGUNAKAN METODE ELEMEN HINGGA - Ikhwal Imam Rezaldy (2022)
Fender is a part of the structure whose function is absorbing the energy from a collision. Marine fender which serves to absorb the energy of the collision of ships to the dock or other ships. These fenders are placed on docks or ships. The impact energy is transferred to the reaction in the wharf structure. loads arising from collisions that can occur at any time on any ship can cause many problems such as those that are significant to the hull, for example, damage, cracks, deformation, and others. The various forms of fenders with different stress distribution values require a local stress analysis with the help of finite element-based software. Finite element method analysis can be done using various software. The author chose to use the ANSYS software. This software was chosen because it can calculate the potential energy of a material with a load that is charged by the ship's berthing energy. The analysis only focuses on fenders, by simulating type M fenders and half pipes attached to RoRo vessel with sizes LPP = 1900t, LBP = 60 m, B = 12 m, and D1 = 4 m. The corresponding abnormal berthing energy Ea = 66.6 kN was calculated using the regulated conditions with VB = 0.15 m/s and CE = 1.0, and took Fs = 2.0. With variations of the angle used are 0°; 2.5 °; 5 °; 7.5°; and 10°. In the analysis, it was found that the M fender has the ability to absorb the given forces with a maximum stress value that is lower than the half-pipe fender's.